Policy Recommendation on the Restriction on Amphibian Trade Toward the Republic of Korea - Borzée, Amaël; Kwon, Sera; Koo, Kyo Soung; Jang, Yikweon (Frontiers in Environmental Science, 2020)
Amphibian diseases and invasive amphibian species are both generally introduced through the wildlife trade, either for human consumption or for the pet trade. However, adequate regulations can prevent such introductions. In the Republic of Korea, the establishment of invasive Lithobates catesbeianus populations resulted in the alteration of native species’ ecology and in an increase in Batrachochytrid load on local species. While not exemplified yet, the same risk arises from all species in the trade, some of which are already found in the wild despite the potential threats to the ecosystems. While regulations exist for the trade of wildlife in general, they are not directly addressing the amphibian trade, especially newly traded species. Thus, we recommend a restriction on the trade of amphibians in Korea.